Metode Design Thinking UI/UX Aplikasi UMKM Sanfresh - Rita Komalasari; Riksania Helga Tsalitsa; Zen Munawar; Novianti Indah Putri (LPPM STMIK IKMI Cirebon, 2023)
Switching to online media is one of the solutions for MSME players to survive during the pandemic at that time, one of which is Sanfresh MSMEs engaged in e-commerce for fresh vegetable and fruit products, even during the Covid-19 pandemic e-commerce is projected to continue to grow, in terms of any business it is to offer a pleasant and useful experience for customers. This research aims to create User interface and User experience of Sanfresh MSME mobile-based applications using the Design thinking method. User interface and user experience of Sanfresh MSME mobile-based applications are expected to be the beginning of a good step to produce an attractive appearance of the application and produce a good experience for users when visiting the application, because that is the most important thing before developing an application.